The snakehead fish Channa aurolineata is a valid species (Teleostei: Channidae) distinct from Channa marulius - Adamson, Eleanor A. S.; Britz, Ralf (Zootaxa, 2018)
Channa aurolineata is a valid species of the Marulius group. Previously treated as a synonym of C. marulius, C. aurolineata is readily distinguished from C. marulius by a different colour pattern, in which a conspicuous white posterior margin is present on the black scales that form the dark lateral blotches in larger juveniles and adults (vs. scales without white margin but with white spots in C. marulius). Channa aurolineata also differs from C. marulius by having more lateral line scales (65–71 vs 62–65), more dorsal-fin rays (55–58 vs 52–56) and more vertebrae (63–66 vs 59–63). In addition to these morphological differences, C. aurolineata is genetically more than 8% different (uncorrected p-distance) from C. marulius at the COI barcoding gene, a difference consistent with levels of genetic divergence observed among different species. The same characters that distinguish C. aurolineata from C. marulius also distinguish it from C. pseudomarulius, the other Indian member of the Marulius group. Channa aurolineata has a widespread distribution in larger rivers in Myanmar, including the Chindwin, Ayeyarwaddy, Sittaung and Thanlwin river basins. The Indo-Burman ranges appear to delineate the western geographical limit of this species, with C. marulius restricted to the western side of this mountain chain.